Nonsymbolic and symbolic magnitude comparison skills as longitudinal predictors of mathematical achievement - Iro Xenidou-Dervou; Dylan Molenaar; Daniel Ansari; Menno van der Schoot; Ernest C.D.M. van Lieshout (2017)
What developmental roles do nonsymbolic (e.g., dot arrays) and symbolic (i.e., Arabic numerals) magnitude comparison skills play in children’s mathematics? In the literature, one notices several gaps and contradictory findings. We assessed a large sample in kindergarten, grade 1 and 2 on two well-known nonsymbolic and symbolic magnitude comparison measures. We also assessed children’s initial IQ and developing Working Memory (WM) capacities. Results demonstrated that symbolic and nonsymbolic comparison had different developmental trajectories; the first underwent larger developmental improvements. Both skills were important longitudinal predictors of children’s future mathematical achievement above and beyond IQ and WM. Nonsymbolic comparison was predictive in kindergarten. Symbolic comparison, however, was consistently a stronger predictor of future mathematics compared to nonsymbolic, and its predictive power at the early stages was even comparable to that of IQ. Furthermore, results bring forth methodological implications regarding the role of different types of magnitude comparison measures.